2018
DOI: 10.1136/tobaccocontrol-2018-054575
|View full text |Cite
|
Sign up to set email alerts
|

Retailers’ perspectives on selling tobacco in a low-income San Francisco neighbourhood after California’s $2 tobacco tax increase

Abstract: BackgroundCalifornia’s tobacco tax increased by $2.00 per pack in 2017. Although such increases are among the most effective tobacco control strategies, little is known about their impact from the perspective of corner store owners in low-income neighbourhoods with high concentrations of tobacco outlets.MethodsWe interviewed 38 corner store owners and managers in San Francisco’s Tenderloin, the district with the city’s highest tobacco outlet density, 60–90 days following implementation of the tax increase. Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Interventions that aid retailers with transitioning from tobacco to alternative product lines may alleviate some of their economic concerns ( Ribisl et al 2016 ). With this assistance, the expected economic benefits to the community—including increased jobs, economic activity, and reduced healthcare costs ( Chaloupka & Glantz, 2021 )—as well as concern for the health of their customers ( Chavez et al 2019 ) may outweigh any short-term financial losses that lessen retail employees’ support for local flavor ordinance.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions that aid retailers with transitioning from tobacco to alternative product lines may alleviate some of their economic concerns ( Ribisl et al 2016 ). With this assistance, the expected economic benefits to the community—including increased jobs, economic activity, and reduced healthcare costs ( Chaloupka & Glantz, 2021 )—as well as concern for the health of their customers ( Chavez et al 2019 ) may outweigh any short-term financial losses that lessen retail employees’ support for local flavor ordinance.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of T21 on purchasing behaviour could have been impacted by one of several other policy changes or campaigns in California during the data collection period. During this time, many anti-tobacco campaigns targeting youth were implemented23–26 and the tax on tobacco products in California was increased (2017) 27. Anti-tobacco campaigns in California or nationally, or increases in the tobacco tax in California, might be expected to supplement T21 and result in changes to overall use and to purchasing behaviour 28–30.…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen studies were conducted in the USA,6 14 17 23–36 three in Australia,37–39 two in the UK,8 15 two in South Korea7 40 and one each in Canada,41 New Zealand,42 and Indonesia 43. The earliest was published in 199114 and the most recent were published in 2020 17 25 38 39.…”
Section: Resultsmentioning
confidence: 99%
“…For example, one retailer interviewed in the UK reported reserving two-thirds of their tobacco unit space for a contracted manufacturer15 and another in the USA recounted that manufacturer representatives required 45% of the tobacco retail space to be dedicated to that particular manufacturer 29. Studies also reported that representatives regularly visited retailers and, to varying degrees, had control over the store design, layout, and placement of tobacco products and advertisements 6 8 15 17 24 27 32 37 40. Slotting fees (ie, payments from the manufacturer to the retailer in exchange for shelf space) were also commonly reported as an incentive in different contracts,7 particularly in the USA 6 17 24 28.…”
Section: Resultsmentioning
confidence: 99%